pengaruh gaya hidup,kualitas produk,dan suasana terhadap keputusan pembelian di green cafe jatinegara - Fitri Nur Aliyah; Meylani Tuti (LPPM Universitas Asa Indonesia, 2023)
This study aims to determine the effect of lifestyle, product quality, and atmosphere on purchasing decisions at Green Café Jatinegara. The population in this study are people who make purchases at the Grand Café. The sampling technique used was accidental sampling, namely respondents who wanted to fill out a questionnaire distributed by researchers with a total of 158 people. Data analysis techniques using the help of smartPLS. The results show that lifestyle has a positive and significant effect on purchasing decisions. Product quality has a positive and significant effect on purchasing decisions. Furthermore, the atmosphere influences the purchase decision.